Antibiotic Stewardship for Ambulatory Urological Procedures: Cystoscopy and Vasectomy. Issue 4 (5th July 2020) - Henry, Mark; Patil, Dattatraya; Filson, Christopher P.; Mehta, Akanksha
Abstract: Introduction: We evaluated physician adherence to antibiotic stewardship for outpatient cystoscopy and vasectomy, which are associated with a low risk of infection and for which prophylactic antibiotics are not routinely recommended. Methods: We used Truven Health MarketScan® data to identify individuals who underwent diagnostic cystoscopy or vasectomy between 2009 and 2015. Prophylactic antibiotic use was captured within a 30-day preprocedural window for oral and a 24-hour preprocedural window for parenteral medication, respectively. We assessed demographic and clinical characteristics such as geographic location as possible covariates impacting preprocedural antibiotic use. Trends in antibiotic use and the impact of covariates were determined using logistic regression models with SAS® v9.4 software. Significance was set as 2-tailed p <0.05. Results: During the study period 1, 060, 199 cystoscopy and 433, 013 vasectomy claims were processed. Prophylactic antibiotics were used in 38% of all cystoscopies and 16% of all vasectomies. Antibiotic use increased throughout the study period for cystoscopy (34.9% to 45.2%, p=0.002) and vasectomy (15.8% to 19.5%, p=0.032). On multivariable analysis younger age and geographic residence in the South were the most important predictors of antimicrobial prophylaxis use for cystoscopy while older age, higher Charlson comorbidity index score and geographic residence in the South were associated with an increased likelihood of prophylactic antibiotic use for vasectomy. Conclusions: Despite evidence-based recommendations against routine prophylactic antibiotics for uncomplicated office procedures like cystoscopy and vasectomy, antibiotic use has increased over time. Overuse of antibiotic prophylaxis has implications for antibiotic resistance and changes in normal microbial flora.